Optimized Location and Assignment of Emergency Response Assets in Offshore Energy Basins (Journal of Applied Business and Economics, 2024)
The global energy industry engages in exploration, drilling, production, and abandonment activities in pursuit of crude oil and natural gas. This paper provides a methodology to optimize the location and assignment of oil spill response containment systems to limit environmental damage. Utilizing 1,802 active offshore sites and 13 eligible service depots in the Gulf of Mexico’s offshore energy basin, this study locates and assigns deployable land-based containment systems while evaluating the progressive enhancement of including additional service depots. The model solves the practical problem of locating and allocating oil spill containment systems to a global optimum. Adding service depots reduces the average distance, or travel time, of response vessels, which minimizes the dispersion of the oil spill. This study represents a critical component of a broader emergency oil spill response plan. Specifically, it addresses the preparation phase of a comprehensive oil spill response plan, which is preceded by the mitigation phase and followed by the response and recovery phases.
Keywords: business; economics; offshore logistics; combinatorial optimization; emergency response